Kepemimpinan Profesional di Tengah Maraknya Kasus Korupsi Dana BOS dalam Dunia Pendidikan - Misdayani Jambak; Putri Maharani; Putri Riskiyah; Ahmad Hasan; Kasman Kasman (CV. ALIM'SPUBLISHING, 2026)
The increasing number of corruption cases involving School Operational Assistance (BOS) funds has become a serious challenge for the education sector in Indonesia. These cases not only undermine public trust in educational institutions but also hinder the achievement of equitable and quality education. This study aims to analyze the role of professional leadership in preventing and addressing the misuse of BOS funds within educational institutions. The research employs a qualitative approach through literature review and analysis of relevant regulations, scholarly publications, and documented corruption cases in the education sector. The findings indicate that professional leadership characterized by integrity, accountability, transparency, and strong ethical commitment plays a significant role in minimizing opportunities for corruption. Effective leaders are able to establish robust internal control systems, promote a culture of honesty, and ensure participatory financial management involving various stakeholders. Furthermore, continuous supervision and adherence to governance principles strengthen institutional resilience against financial misconduct. The study implies that strengthening leadership capacity and ethical values among educational leaders is essential for improving financial governance and fostering public confidence in educational management. Professional leadership is therefore a crucial factor in supporting clean, transparent, and sustainable education administration.